SISTEM INFORMASI GEOGRAFIS BERBASIS MOBILE ANDROID UNTUK PEMETAAN LOKASI PENGRAJIN KERAJINAN TANGAN KHAS GORONTALO - irfan abbas (Jurnal Informatika Upgris, 2017)
Gorontalo handicraft industry is already widespread in the territory of Indonesia, and even then more introduced by the people of Gorontalo in overseas. In early 2006, Gorontalo's unique handicraft products received attention from both central and provincial governments to fight for patents on products (Hinelo, 2008). It shows that the creative industry business run by the Gorntalo Society has been well developed. The researcher intends to design a mobile geographic information system based on android for mapping the location of craftsmen typical of Gorontalo handicraft. This system is the application of GIS mobile system that is integration between three technology, that is GIS software, Global Positioning System (GPS) technology, and mobile device. This mobile-based designed system is intended to make this system easier to use by the Community because the system can be accessed simply by using a mobile device. While android is a mobile phone operating system that grows in the middle of other operating systems that develop this dewasi. This system will provide location information dilegkapi with travel routes as well as a description of the handicraft industry selected by the user / community. This system will provide location information dilegkapi with travel routes as well as a description of the handicraft industry selected by the user / community. With this system will be able to provide convenience to anyone who wants to find the location / location of handicraft industry typical Karawo patterned clothing Gorontalo. This system can run well based on testing on system logic using whitebox method obtained value of Ciclometic Complexity (CC) = 3. Keywords: Geographic Information System, Android, Karawo